Quadratic general rotary unitized design for doping concentrations and up-conversion luminescence properties of Er3+/Yb3+ co-doped NaLa(MoO4)2 phosphors. (August 2016) - Sun, Jiashi; Shi, Linlin; Li, Shuwei; Li, Jingjing; Li, Xiangping; Zhang, Jinsu; Cheng, Lihong; Chen, Baojiu
Graphical abstract: Highlights: NaLa(MoO4)2: Er3+/Yb3+ phosphor is synthesized by solid state method. QGRUD is first applied to the codoping concentration option. Optimized phosphor presents more stable UC emissions than the commercial phosphor. Abstract: It is still a great challenge that designing proper codoping concentrations of rare earth ions for achieving intensest expected emission from the studied phosphor. In this work, the quadratic general rotary unitized design (QGRUD) was introduced into the codoping concentration option of NaLa(MoO4 )2 : Er 3+ /Yb 3+ phosphor for upconversion (UC) applications, and the optimum doping concentrations of Er 3+ and Yb 3+ for achieving maximum UC luminescence intensity, which is close to commercial NaYF4 :Er 3+ /Yb 3+ phosphor, were obtained. The two-photon process was assigned to the green UC emissions in the optimized NaLa(MoO4 )2 : Er 3+ /Yb 3+ phosphor. It was also demonstrated that the optimized phosphor presented more stable upconversion emissions than the commercial NaYF4 :Er 3+ /Yb 3+ phosphor.